MicroRNA-155-5p in pathogenesis of cancer - I. B. Zborovskaya; A. V. Komel’kov (Успехи молекулярной онкологии)
MicroRNA miR-155 is one of the most characterized and actively studied microRNAs that regulate processes closely related to carcinogenesis, including cell differentiation, adhesion, migration and invasion of the tumor cells, metastasis, apoptosis and immunosuppression.  In addition, this miRNA is involved in differentiation of hematopoetic cells and developing of inflammation. The association between specific deregulation of the expression of miR-155 and carcinogenesis is confirmed by a number of both fundamental and clinical studies and is due to the posttranscriptional regulation of the most important genes of the tumor associated pathways. Modulation of the levels of expression  of miR-155 is associated with the emergence of a number of leukemias and lymphomas, as well as some solid tumors. An increase of the level of cellular and/or circulating miR-155 in some cancers can serve as a marker for progression and drug resistance. In addition, inhibition  of the expression of miR-155 can be a promising method for developing new approaches in antitumor therapy.